Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-70928-2_22
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution versus Genetic Algorithms in Multiobjective Optimization

Abstract: Abstract. This paper presents a comprehensive comparison between the performance of state-of-the-art genetic algorithms NSGA-II, SPEA2 and IBEA and their differential evolution based variants DEMO NS-II , DEMO SP2 and DEMO IB . Experimental results on 16 numerical multiobjective test problems show that on the majority of problems, the algorithms based on differential evolution perform significantly better than the corresponding genetic algorithms with regard to applied quality indicators. This suggests that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 16 publications
(22 reference statements)
2
61
0
Order By: Relevance
“…DE outperforms the above-mentioned prominent algorithms in terms of least number of generations for finding global minimum [15]. Similar results are reported in the following studies [16][17][18]. Hegery et al [16] carried out comparisons between DE and GA on N-Queen and travelling salesman problem and concluded that the performance of DE is better.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…DE outperforms the above-mentioned prominent algorithms in terms of least number of generations for finding global minimum [15]. Similar results are reported in the following studies [16][17][18]. Hegery et al [16] carried out comparisons between DE and GA on N-Queen and travelling salesman problem and concluded that the performance of DE is better.…”
Section: Introductionsupporting
confidence: 69%
“…Hegery et al [16] carried out comparisons between DE and GA on N-Queen and travelling salesman problem and concluded that the performance of DE is better. Tušar and Filipič [17] carried out comparisons between DE-based variants DEMO and basic GA on multiobjective optimization problem and their result showed that DEMO outperforms basic GA. Vesterstrøm and Thomsen [18] noted that DE outperforms PSO and Evolutionary Algorithms (EAs) on majority of numerical benchmark problems. DE consists of population size (NP), scaling factor ( ), and crossover rate (CR) which significantly affect the performance of DE [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for most of the scenarios considered, the DE operator did not improve the performance of the original MOEA/D. Since related work has shown that DE variation can often improve the performance of other algorithms [22], we hypothesize that the interaction between the decomposition approach and DE is responsible for this.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, a more accurate methodology for coordinate optimization is highly desirable, as investigated herein. The evaluation of εDE as an optimization method for this critical task was inspired by previous results obtained for other types of optimization problems where this approach displayed better performance than alternative evolutionary methods, such as genetic algorithms or particle swarm optimization [27][28][29] . Moreover, ε-based lexicological comparison of individual feature vectors makes this algorithm straightforward to apply to problems where several constraints must be balanced, as is the case in inverse QSAR.…”
Section: Resultsmentioning
confidence: 99%